Answer:
(-3, 8)
Explanation:
We are given two equations and we have to find the solution to the given equations. We can do this by using substitution method as shown below:
Equation 1
Equation 2
From Equation 1, we can get the value of y as:
Equation 3
Using this value of y in equation 2, we get:
![x-3(2-2x)=-27\\\\ x-6+6x=-27\\\\ 7x=-21\\\\ x=-3](https://img.qammunity.org/2020/formulas/mathematics/high-school/j6tta153dmxn7hrjyv4sv3y2wn29aglmzs.png)
Thus value of x is -3. Using this value in Equation 3, we get:
![y=2-2(-3)\\\\ y=2+6\\\\ y=8](https://img.qammunity.org/2020/formulas/mathematics/high-school/o9ule7g8q8ur9z57lknc1u4jnrpztui2q6.png)
Thus the solution to the given equations is (-3, 8)